Association between HMGB1 and COPD: A Systematic Review - Sebastiano Gangemi; Marco Casciaro; Giovanni Trapani; Sebastiano Quartuccio; Michele Navarra; Giovanni Pioggia; Egidio Imbalzano (Hindawi Limited, 2015)
HMGB1 is an alarmin, a protein that warns and activates inflammation. Chronic obstructive pulmonary disease (COPD) is characterised by a progressive airflow obstruction and airway inflammation. Current anti-inflammatory therapies are poorly effective in maintaining lung function and symptoms of COPD. This underlines the need for finding new molecular targets involved in disease pathogenesis in order to block pathology progression. This review aims to analyse latest advances on HMGB1 role, utilisation, and potential application in COPD. To this purpose we reviewed experimental studies that investigated this alarmin as marker as well as a potential treatment in chronic obstructive pulmonary disease. This systematic review was conducted according to PRISMA guidelines. In almost all the studies, it emerged that HMGB1 levels are augmented in smokers and in patients affected by COPD. It emerged that cigarette smoking, the most well-known causative factor of COPD, induces neutrophils death and necrosis. The necrosis of neutrophil cells leads to HMGB1 release, which recruits other neutrophils in a self-maintaining process. According to the results reported in the paper both inhibiting HMGB1 and its receptor (RAGE) and blocking neutrophils necrosis (inducted by cigarette smoking) could be the aim for further studies.